Pivotal Reactions in the Creation of the Polycyclic Skeleton of Cryptotrione - Zhong, Zhuliang; Lyu, Mao-Yun; Ma, Hao-Ran; Wong, Henry N. C.; Peng, Xiao-Shui (Synlett, 2021)
Three pivotal reactions, namely, enyne cycloisomerization, polyene cyclization, and quinone methide formation, are applied to synthesize the complex polycyclic skeleton of cryptotrione. This review summarizes the most prominent applications of these three reactions to the total syntheses of natural products, covering results published in the literature between 2011 and 2020.1 Introduction2 Three Pivotal Reactions Applied to Create the Polycyclic Framework of Cryptotrione2.1 Enyne Cycloisomerization2.2 Polyene Cyclization2.3 Quinone Methide Formation3 Conclusion
Keywords: total synthesis; natural products; enyne cycloisomerization; polyene cyclization; quinone methides